Circumscribed palmar or plantar hypokeratosis: Report of an Italian case - D Tosi; F Sala; C Crosti (Wolters Kluwer Medknow Publications, 2011)
Circumscribed palmar or plantar hypokeratosis is a rare benign epidermal malformation of the skin. Clinically it shows asymptomatic, well-circumscribed, and depressed erythema persisting for many years on the palms or soles. Its main histopathologic feature shows a characteristic epidermal depression with an abrupt decrement in the thickness of the stratum corneum, with a sharp stair between normal and involved skin. We describe a case of a 68-year-old woman who presented with an erythematous, asymptomatic, well-circumscribed, depressed patch, on the right thenar eminence which had been present for years.